Chironomid head capsules for the Holocene sediment sequence retrieved from Lake Loitsana, Finland - Shyhrete Shala; Karin Helmens; Stefan Engels; Peter Kuhry; Malin E Kylander; Tomi P Luoto; Sakari Salonen; Minna Väliranta; Jan Weckström (PANGAEA, 2025)
This dataset provides counts of chironomid head capsules for the Holocene sediment sequence retrieved from Lake Loitsana (Finland) in 2008. Counts per taxon are presented against both depth (m) and age (cal ka. BP). Two age/depths models are presented: the first model represents the original age/depth model applied to the records (Shala et al., 2014b; 2017) and the second age/depth model, which is the author-preferred version, presents updated age-estimates derived using the r package extquotesingleBacon extquotesingle (Blaauw and Christensen, 2011). The chironomid dataset provides information on Holocene lake ecosystem dynamics and was used to quantitatively reconstruct local climate conditions. A total of 71 samples from the Holocene sediment sequence were treated with warm KOH (10%) to de-flocculate the material and subsequently rinsed through a sieve with a 100-μm mesh. Chironomid head capsules (HCs) were hand-picked from the residue using a Bogorov sorting tray and mounted on permanent microscope slides using Euparal mounting medium. HCs were identified using Brooks et al. (2007). A minimum of 50 midge individuals was identified from each sample with the exception of the lowermost two samples of the sequence, where head capsule concentrations were extremely low. All analyses were performed in the laboratories of the University of Helsinki, Finland.